Pervasive gene expression responses to a fluctuating diet in Drosophila melanogaster: The importance of measuring multiple traits to decouple potential mediators of life span and reproduction. (1st November 2017) - Zandveld, Jelle; van den Heuvel, Joost; Mulder, Maarten; Brakefield, Paul M.; Kirkwood, Thomas B. L.; Shanley, Daryl P.; Zwaan, Bas J.
Abstract: Phenotypic plasticity is an important concept in life‐history evolution, and most organisms, including Drosophila melanogaster, show a plastic life‐history response to diet. However, little is known about how these life‐history responses are mediated. In this study, we compared adult female flies fed an alternating diet (yoyo flies) with flies fed a constant low (CL) or high (CH) diet and tested how whole genome expression was affected by these diet regimes and how the transcriptional responses related to different life‐history traits. We showed that flies were able to respond quickly to diet fluctuations throughout life span by drastically changing their transcription. Importantly, by measuring the response of multiple life‐history traits we were able to decouple groups of genes associated with life span or reproduction, life‐history traits that often covary with a diet change. A coexpression network analysis uncovered which genes underpin the separate and shared regulation of these life‐history traits. Our study provides essential insights to help unravel the genetic architecture mediating life‐history responses to diet, and it shows that the flies' whole genome transcription response is highly plastic.